Cardiorespiratory fitness and left atrial strain in atrial fibrillation: A comparative study. (11th May 2021) - Mishima, RS; Ariyaratnam, JP; Malik, V; Pitman, BM; Elliott, AD; Sanders, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atrial fibrillation (AF) is the most common clinically relevant arrhythmia, and its occurrence is associated with pathological left atrial (LA) remodelling. In these patients, low cardiorespiratory fitness (CRF) is associated with increased AF recurrence. Speckle tracking derived LA strain (LAS) permits chamber function quantification and provides angle-independent and highly reproducible measurements of chamber deformation. However, the relationship between CRF and LA function, amongst AF patients is poorly understood. Purpose: To compare LA function amongst AF patients stratified by cardiorespiratory fitness. Methods: Consecutive AF patients referred for treadmill exercise stress test (EST) and transthoracic echocardiogram (TTE) between March and December 2020 were screened for inclusion. Treadmill EST was symptom limited and age and gender predicted CRF was calculated with conventional formulas. Speckle tracking software was used to obtain LAS from apical 4 and 2 chamber views and mean measurements for LASr and LASb were calculated. Those achieving <100% (low CRF) and ≥100% (high CRF) of predicted CRF were compared. Results: After exclusions, 141 patients in sinus rhythm were included in the analysis. Baseline characteristics were not significantly different between groups. Ejection fraction (63.6 ± 4.7% vs 64.8 ± 8.4%, p = 0.3) and LA volume index (33.1 ± 6.9 vs 31.4 ± 9.4 mL/m2, p = 0.3) were not different between groups. Both LASr (22.9% ± 7.4% vs 27.6% ± 11.4%, p = 0.02) and LASb (8.2% ± 4.7% vs 12.1% ± 6.8%, p = 0.004) (figure 1) were significantly higher in the fitter group. Conclusion: Patients with higher CRF showed improved LA function as per strain measurement in the absence of AF. The relationship between CRF and left atrial function warrants further research.